The Colonial Funeral Elegy: Carlos III and the Rhetoric of Mourn (Part I) - Altamirano Pacheco, Sebastián (2020)
The investigation bases on the Latin elegies from the article: Description of the real funeral to the dearest memory of Carlos III (1789), which seeks to identify, precisely, the elegiac elements related to the Latin speech of the laudatio funebris from the rhetorical classical theory. The theoretical framework consists on the rhetorical perceptive from Anaximenes from Lampsacus, Aristotle, Rhetorica ad Herennium, Menander Rhetor, Theon, Hermogenes of Tarsus, and Aphthonius.